GBIF Occurrence Download - Occdownload Gbif.Org (The Global Biodiversity Information Facility, 2016)
A dataset containing 48359 species occurrences available in GBIF matching the query: TaxonKey: Antennaria dioica (L.) Gaertn. HasCoordinate: true HasGeospatialIssue: false. The dataset includes 48359 records from 201 constituent datasets: 25 records from Marie-Victorin Herbarium (MT) - Plantes vasculaires. 99 records from University of British Columbia Herbarium (UBC) - Vascular Plant Collection. 45 records from Phanerogamic Botanical Collections (S). 317 records from Jordal. 1 records from University of Vienna, Institute for Botany - Herbarium WU. 16 records from Online Atlas of vascular plants 2012-2020. 1 records from IAC - Herbário do Instituto Agronômico de Campinas. 15 records from Naturalis Biodiversity Center (NL) - Botany. 2 records from PlutoF platform observations. 1 records from SP - Herbário do Estado "Maria Eneyda P. Kaufmann Fidalgo" - Coleção de Fanerógamas. 6 records from Plant Specimen from Herbarium (HIB) in China, Wuhan Botanical Garden, Chinese Academy of Sciences. 57 records from Species plots from the Norwegian Vegetation Mapping Programme. 179 records from FLORIVON. 261 records from Species data extracted from the National Vegetation Database. 62 records from Vascular plants in Denmark recorded under the The Nationwide Monitoring and Assessment Programme for the Aquatic and Terrestrial Environments (NOVANA). 268 records from University of Alberta Vascular Plant Herbarium (ALTA-VP). 3 records from Some Plant Specimens from KUN, IBSC, NAS Herbarium in China from 1900 to 1950. 10 records from Plant Specimen from Herbarium (CDBI) in China, Chengdu Institute of Botany, Chinese Academy of Sciences. 6 records from Inventaire National du Patrimoine Naturel : Flore de l'Ain. 72 records from Florabank1 - A grid-based database on vascular plant distribution in the northern part of Belgium (Flanders and the Brussels Capital region). 936 records from BioFokus. 33 records from Herbier Louis-Marie (QFA) - Collection de plantes vasculaires. 130 records from Vascular plant herbarium, Agder naturmuseum og botaniske hage. 10171 records from Artdata. 3 records from Stabbetorp - Floristiske registreringer 2016. 240 records from OHN. 54 records from Données ONF Faune-Flore-Fonge. 5 records from John Muir Trust - Plants, Bryophytes and Lichens recorded on the Skye Estate during October 1995 â October 2004.. 1 records from Herbarium areqvipense (HUSA). 2 records from Norwegian Biodiversity Information Centre - Other datasets. 18 records from Australia's Virtual Herbarium. 398 records from Fundación Biodiversidad, Real Jardín Botánico (CSIC): Anthos. Sistema de Información de las plantas de España. 61 records from Vascular Plant Herbarium, UiB. 51 records from Kathryn Kalmbach Herbarium. 3 records from Banco de Germoplasma del Jardín Botánico Atlántico. 3 records from Natural History Museum Maastricht (NL) - Herbarium. 792 records from Consortium of California Herbaria. 34 records from iNaturalist Research-grade Observations. 7 records from CONN. 11 records from H.A. Stephens Herbarium. 11 records from University of Lethbridge Herbarium (LEA). 4 records from LSU Shirley C. Tucker Herbarium at Louisiana State University - Vascular Plants. 8 records from Estonian Museum of Natural History. 3 records from Collection botanique Le Grand A. (BOUM). 24 records from Vegetation data from sheep grazing experiment at alpine site in Hol, Norway. 6 records from NINA botanical collection. 5928 records from Meadow and Pasture Inventory (SJV). 1 records from Banco de Germoplasma de la Universidad Rey Juan Carlos. 312 records from UAM Herbarium (ALA), Vascular Plant Collection (Arctos). 1 records from NMNH occurrence DwC-A. 81 records from Herbarium of the Department of Natural Forests (Forest Research Institute). 2 records from Garten J. Scherrer (Lachen-Speyerdorf). 16 records from Geneva Herbarium – De Candolle's Prodromus (G-DC). 1 records from Naturschutzgebiet Börstig bei Hallstadt. 1166 records from Occurrence Data of Vascular Plants collected or compiled for the Flora of Bavaria. 8 records from Countryside Council for Wales - Phase 2 Lowland Grassland Survey of Wales. 2 records from flower availability 2008 Alb-korrigiert. 1 records from Naturhistorisches Museum Mainz, Herbarium Oesau. 9 records from Naturhistorisches Museum Mainz, Feldbeobachtungsdaten Pflanzen. 143 records from naturgucker. 2 records from flower visitor interactions 2008. 1 records from The Distribution Atlas of Butterflies in Poland. 1 records from John Muir Trust - Plants, Bryophytes and Lichens recorded on the LÃ¬ and Coire Dhorrcail Estate during June 2001.. 1 records from The Flora of County Wexford. 207 records from Dutch Vegetation Database (LVD). 7990 records from INPN - Données flore des CBN agrégées par la FCBN. 1 records from Cartografía de vegetación a escala de detalle 1:10.000 de la masa forestal de Andalucía. 3 records from Royal Botanic Garden Edinburgh Living Plant Collections (E). 35 records from Tiroler Landesmuseum Ferdinandeum. 1 records from The Vascular Plant Collection at the Botanische Staatssammlung München. 438 records from IBF Monitoring of Vascular Plants. 103 records from BSBI tetrad data for Ireland. 27 records from Tropicos Specimen Data. 11 records from Natural History Museum (London) Collection Specimens. 26 records from Catálogo Florístico Histórico de Navarra. Gobierno de Navarra. 14 records from Natural History Museum, Vienna - Herbarium W. 19 records from Ireland's BioBlitz. 6 records from Karl Franzens University of Graz, Insitute for Botany - Herbarium GZU. 1 records from Colección científica del Museo de Historia Natural Alfredo Dugés. 2 records from Universidad de Barcelona. Grup dInvestigació Geobotánica i Cartografia de la Vegetació. 1 records from Herbarium of Lars Levi Laestadius. 1 records from Universität Salzburg. 37 records from The Himalayan Uplands Plant database (HUP Version 1). 95 records from Canadian Museum of Nature Herbarium. 189 records from Vascular Plant Collection - University of Washington Herbarium (WTU). 8 records from Colección de plantas vasculares del herbario de la Universitat de València (VAL).. 17 records from Herbario de Plantas Vasculares de la Universidad de Salamanca: SALA. 17 records from Real Jardín Botánico (Madrid), Vascular Plant Herbarium (MA). 5 records from Universidad del País Vasco/EHU, Bilbao: Herbario BIO. 4 records from Universidad de Oviedo. Departamento de Biología de Organismos y Sistemas: FCO. 3 records from Jardín Botánico de Córdoba: Herbarium COA. 12 records from Aranzadi Zientzi Elkartea. 6 records from CIBIO, Alicante:ABH-GBIF. 5 records from Herbarium of Vascular Plants Collection of the University of Extremadura (Spain). 2 records from Herbario de la Universidad de Sevilla. 4 records from Herbario HSS Finca La Orden-Valdesequera (CICYTEX). Gobierno de Extremadura. 13 records from Institut Botanic de Barcelona, BC. 1 records from Botanic Garden of the Finnish Museum of Natural History. 189 records from Herbarium of Jyväskylä University Museum. 168 records from Vascular Plant Collection. 6 records from Botany registration database by Danish botanists. 14 records from DAV UC Davis Center for Plant Diversity. 11 records from Herbarium Berolinense. 205 records from Observations du Conservatoire botanique national du Bassin parisien.. 23 records from Biologiezentrum Linz. 2 records from United States National Plant Germplasm System Collection. 73 records from USU-UTC Specimen Database. 3 records from Institut Botanic de Barcelona, BC-Histórico. 6 records from Harvard University Herbaria. 5 records from Vascular plants of south-central China. 1 records from Specimen Database of Colorado Vascular Plants. 52 records from inatura - Erlebnis Naturschau Dornbirn. 1 records from EURISCO, The European Genetic Resources Search Catalogue. 88 records from Biodiversitätsdatenbank des Landes Salzburg. 25 records from Vascular Plants, Observations, Oslo (O). 7 records from Programa de repatriación de datos de ejemplares mexicanos. 5 records from FloVegSI - Floristical and fitocenological database of ZRC SAZU. 1 records from Schlern - (Bozen). 1 records from GEO Hauptveranstaltung Tirol (Innsbruck). 1 records from Königstetten. 1 records from NSG Karwendel. 1 records from Wildes Bremer Leben im Park. 1 records from Gemeindegebiet Weikendorf (Marchfeld). 1 records from Prophetensee Quickborn. 1 records from Natural History Museum, University of Tartu. 46 records from Herbarium of Umeå University (UME). 33 records from Base de datos de plantas vasculares del País Vasco: ARAN-EH. 17 records from Belgian IFBL Flora Checklists (1939-1971). 6 records from Inventaire National du Patrimoine Naturel : Flore Franco-Belge. 1 records from Perchtoldsdorfer Heide. 144 records from Colorado State University Herbarium. 122 records from R. L. McGregor Herbarium Vascular Plants Collection. 2 records from EDIT - ATBI in Mercantour/Alpi Marittime (France/Italy). 2 records from EDIT - ATBI in Gemer area (Slovakia). 1 records from Artenvielfalt am Schlern. 1 records from Vom Gipfel ins Moor, Transekt im NSG Allgäuer Hochalpen. 3 records from Jardín Botánico Atlántico, Gijón: JBAG. 9 records from Biological and palaeontological collection and observation data MNHNL. 4 records from Universidad de Oviedo. Departamento de Biología de Organismos y Sistemas: FCO-Briof. 1 records from Database of Native Plants in Taiwan. 1 records from E39 Lyngdal - Ålgård. 26 records from VIT Herbarium - Vascular Plants (The Natural History Museum of Alava). 1 records from Vascular Herbarium, NMBU. 7 records from Wetland Inventory (NV). 1023 records from FloraCAT: Banco de datos de los cormófitos de Cataluña. 10 records from Faun. 28 records from Flora d'Andorra. 1 records from ArtenFinder. 630 records from Lund Botanical Museum (LD). 26 records from vegetation releves on grassland gridplots 2007-2009. 7 records from Geographically tagged INSDC sequences. 20 records from vegetation releves on grassland gridplots in 2007. 3 records from Fieldjournal.org observation database. 3110 records from Norwegian Species Observation Service. 32 records from Irish vascular plant data 1999-2009. 12 records from University of Manitoba Herbarium (WIN) - Vascular Plant Collection. 7 records from Vascular Plants, Museum of Archaeology, University of Stavanger. 1 records from Plant Specimen from Herbarium (IBK) in China, Guangxi Institute of Botany, Chinese Academy of Sciences. 2 records from The vascular plants collection (P) at the Herbarium of the Muséum national d'Histoire Naturelle (MNHN - Paris). 1 records from John Muir Trust - Plants and Bryophytes recorded on Schiehallion 25-30 June 2000. 54 records from Carnet en Ligne. 1 records from Field Study Group of the Dutch Mammal Society (NL) - 2010 - Mammal Survey Patvinsuo National Park, northern Karelia, Finland. 1 records from The Flora of County Wexford. 1 records from Royal Botanic Garden Edinburgh Herbarium (E). 9 records from Flora of County Cavan. 83 records from National Forest Inventory (SLU). 1 records from Herbier du Québec (QUE) – Collection de plantes vasculaires. 2 records from University of British Columbia Botanical Garden Collections (UBCBG). 26 records from Estonian Nature Observations Database. 7 records from The Flora of County Clare. 4 records from Verneplan Hjerkinn karplanter. 4 records from Kartlegging av dragehode. 323 records from Vascular plant herbarium, NTNU University Museum. 54 records from Données ONF Faune-Flore-FOnge. 4929 records from Vascular Plants, Field notes, Oslo (O). 16 records from The New York Botanical Garden Herbarium (NY) - Vascular Plant Collection. 956 records from Sistema de Información de la vegetación Ibérica y Macaronésica. 17 records from Vegetation data from protected areas in Denmark (§ 3 in the Danish Nature Protection Act). 10 records from Universidad de Navarra, Herbarium: PAMP-Vascular Plants. 20 records from Ecofact. 2 records from Green Plant Herbarium (TRT). 1 records from John Muir Trust - Plants, Bryophytes and Lichens recorded on Quinag in 2006-2007. 110 records from Floristic Databases of Mecklenburg-Pomerania - Higher Plants. 1 records from Herbarium of University of Białystok - Vascular Plants. 68 records from A grid-based database on vascular plant distribution in the Meshchera National Park, Vladimir Oblast, Russia. 328 records from Vascular Plant Herbarium, Oslo (O). 2656 records from Flora von Deutschland (Phanerogamen). 1 records from Suffolk Biological Records Centre - Suffolk Biological Records Centre (SBRC) dataset. 3 records from E. C. Smith Herbarium (ACAD). 1 records from SWECO. 2 records from Herbario de Plantas Vasculares de la Asociación BIGA para el estudio del patrimonio natural de Galicia: FBIGA. 4 records from John Muir Trust - Plants, Bryophytes and Lichens recorded on the Sandwood Estate during 1998 â 2006.. 1 records from Herbier Boreal Confluence (BOUM). 7 records from National Trust for Scotland - NTS Properties Species Records 1800-2013. 912 records from Vascular plant field notes, NTNU University Museum. 1 records from SysTax - Herbaria. 1 records from John Muir Trust - Plants, Bryophytes and Lichens recorded on the Nevis Estate during summer 2003.. 1 records from Geneva Herbarium – General Collection (G). 42 records from Some Plant Specimens from PE Herbarium in China from 1900 to 1950. 24 records from CAS Botany (BOT). 8 records from Vegetation releves in 150 grassland EPs in 2008. Data from some individual datasets included in this download may be licensed under less restrictive terms.
Keywords: GBIF; biodiversity; species occurrences